IMPLEMENTASI KEBIJAKAN PELAPORAN ON-LINE KEUANGAN - Harapan Tua, Rohani, Tri Sukirno Putro, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Financial Online Reporting Policy. This study aims to find out analyzing the implementation of the on-line reporting policy with Presidential Decree number 20 of 2015 concerning the Evaluation and Supervision Team for the Realization of the State Revenue and Expenditure Budget and the Regional Budget and Budget. This type of research is qualitative. The research informants consisted of key informants, key informants and additions. Methods of data collection are interviews, observation and documentation. Based on the results of the study Implementation of this online reporting policy is still not optimal, as is the case with problems that are still not optimal policy goals and objectives in the sense that they have not been well socialized to all staff working in their fields, then the problem of budget constraints to finance all supporting facilities for this policy . Factors that hinder the implementation of the policy of implementing online reporting in the transportation agency of the Kampar district is that the objectivity is still low, the assessment is only for those who have the ability, while those who have worked long but the limited ability to understand finally they cannot do what they should do it.